Framing Climate Change: Economics, Ideology, and Uncertainty in American News Media Content From 1988 to 2014 - Stecula, Dominik A.; Merkley, Eric (Frontiers in Communication, 2019)
The news media play a seminal role in shaping public attitudes on a wide range of issues – climate change included. As climate change has risen in salience, the average American is much more likely to be exposed to news coverage now than in the past. Yet, the content of these news stories has been underexplored in academic literature, despite likely playing an important part in fostering or inhibiting public support and engagement in climate action. In this paper we use a combination of automated and manual content analysis of the most influential media sources in the U.S., including the New York Times, Wall Street Journal, the Washington Post, and the Associated Press, to illustrate the prevalence of different frames in the news coverage of climate change and their dynamics over time. We focus on three types of frames, based on previous research: economic costs and benefits associated with climate mitigation, appeals to conservative and free market values and principles, and uncertainties and risk surrounding climate change. We find that many of the frames found to reduce people’s propensity to support and engage in climate action have been on the decline in the mainstream media, such as frames emphasizing potential economic harms of climate mitigation policy or uncertainty. At the same time, frames conducive to such engagement by the general public have been on the rise, such as those highlighting economic benefits of climate action. News content is also more likely now than in the past to use language emphasizing risk and danger, and to use the present tense. To the extent that citizens may not be informed of the gravity of the risk posed by uncontrolled greenhouse gas emissions, or discount threats that appear to be far in the future, these are welcome developments.